Psychopathology and Family Functioning in Adolescents with Beta Thalassemia - S. Adanır, Aslı; Taskıran, Gulseren; Cıgıl Fettahoglu, Emine; Ozatalay, Esin (Adolescent Psychiatry, 2017)
Objective: As all the chronic diseases, thalassemia is physically and psychologically demanding for both the child and family. Previous studies reported that children with thalassemia had a higher risk of psychopathology. The aim of the present study was to investigate the prevalence of psychopathology in adolescents with β-thalassemia and the family functioning in their families. Methods: The study group consisted of 24 adolescents (aged 12-18) with β-thalassemia and one of their parents (mother or father). A control group of 20 adolescents matched for gender and age and one of their parents were randomly chosen from the schools of the hospital environment, and screened by a short face-to-face interview to exclude any medical illness or previous application to child psychiatry clinics. All children and parents were invited to the clinic and interviewed by a child psychiatrist then. Psychopathology in adolescents was assessed with Kiddie Schedule for Affective Disorders and Schizophrenia-Present and Lifetime Version, a semi-structured schedule for assessing psychopathology in children and adolescents. All adolescents and their parents also completed McMaster Family Assessment device (FAD), a self-report scale to assess family functioning in various domains. Results: The life-long prevalence of psychiatric disorders was found to be significantly higher in the patient group compared to the control group consistent with the literature, and anxiety disorders were found to be almost 2 times higher (70%) than the previous studies, indicating an increase in anxiety rates in this population. Statistical analysis of the FAD showed that the patient group had significantly higher subscores in nearly all areas, indicative of problems in family functioning, compared to the control group. The mean educational level of parents was significantly lower in the patient group, and families with poorly-educated fathers were at a higher risk of having a second thalassemic child. Conclusion: These results point to the importance of psychosocial support in chronic conditions, especially in thalassemia and to the value of multi-systemic interventions, which target not only child's medical condition but also the possible psychopathology of child and the functioning of the family
Keywords: psychiatric disorders